Attenuation of the effects produced by the bending modes of a flexible launch vehicle using second order filters - Boglis, Ioana-Carmen; Stoica, Adrian M. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This article describes the application of an adaptive control algorithm for the atmospheric phase control of a launch vehicle. A dynamic model representing the pitch motion of the launch vehicle is introduced. As the bending modes can cause instability, the first three bending modes are modelled. A case study on design of the bending filters for a flexible launch vehicle using a model reference adaptive control is conducted to demonstrate its effectiveness.